The presence of Homo in Sicily: evidence, hypotheses and uncorroborated ideas. An archaeo-anthropological perspective - Portaro, Claudia; Varotto, Elena; Sineo, Luca; Galassi, Francesco M. (Anthropological Review, 2024)
This article summarises the main findings and data on the ancient peopling of the Mediterranean island of Sicily through an archaeo-anthropological perspective. The hypothesis surrounding the presence of the Lower Palaeolithic in Sicily with more ancestral species of Homo is also extensively reviewed and it is explained why there are not sufficient elements to maintain it. Finally, future multidisciplinary proposals are made to fill the gap on Sicilian cave archaeology.